A threatened species index for Australian birds. Issue 2 (9th December 2020) - Bayraktarov, Elisa; Ehmke, Glenn; Tulloch, Ayesha I. T.; Chauvenet, Alienor L.; Avery‐Gomm, Stephanie; McRae, Louise; Wintle, Brendan A.; O'Connor, James; Driessen, Joris; Watmuff, James; Nguyen, Hoang Anh; Garnett, Stephen T.; et al.
Abstract: Quantifying species population trends is crucial for monitoring progress towards global conservation targets, justifying investments, planning targeted responses and raising awareness about threatened species. Many global indicators are slow in response and report on common species, not on those at greatest risk of extinction. Here we develop a Threatened Species Index as a dynamic tool for tracking annual changes in Australia's imperiled birds. Based on the Living Planet Index method and containing more than 17, 000 time series for 65 bird taxa surveyed systematically, the index at its second iteration shows an average reduction of 59% between 1985 and 2016, and 44% between 2000 and 2016. Decreases seem most severe for shorebirds and terrestrial birds and least severe for seabirds. The index provides a potential means for measuring performance against the Convention on Biological Diversity's Aichi Target 12, enabling governments, agencies and the public to observe changes in threatened species.